Analyzing the potential of neuronal pentraxin 2 as a biomarker in neurological disorders: A literature review - Ubaid Ansari; Jimmy Wen; Burhaan Syed; Dawnica Nadora; Romteen Sedighi; Denise Nadora; Vincent Chen; Forshing Lui (AIMS Neuroscience)
Neuronal pentraxin 2 (NP2) plays a significant role in synaptic plasticity, neuronal survival, and excitatory synapse regulation. Emerging research suggests that NP2 is implicated in the pathogenesis of various neurological disorders, including neurodegenerative diseases, neuropsychiatric disorders, and neuropathies. This literature review extensively analyzes NP2's role in these conditions, thereby highlighting its contributions to synaptic dysfunction, neuroinflammation, and neurotoxic protein aggregation. In Alzheimer's and Parkinson's diseases, NP2 is linked to amyloid-beta aggregation and dopaminergic neuron degeneration, respectively. Additionally, altered NP2 expression is observed in schizophrenia and bipolar disorder, thus suggesting its involvement in synaptic dysfunction and neurotransmitter imbalance. In neuropathic pain and epilepsy, NP2 modulates the synaptic plasticity and inflammatory responses, with altered levels correlating with disease severity. Furthermore, NP2's involvement in amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) emphasizes its broad impact on neuronal health. Understanding NP2's multifaceted roles may reveal novel therapeutic targets and improve the clinical outcomes for these neurological disorders. Though the precise role of NP2 remains uncertain, its clinical potential and initial findings justify further investigations into neuronal pentraxins and other related neuroproteins.